Menelusuri Penggunaan Media Sosial Mahasiswa Generasi Z di Takengon: Dampak pada Komunikasi dan Sosial - Sri Widari; Rudianto, Rudianto; Ginting, Rahmanita (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2024)
Generation Z students in Takengon City are a generation of active social media users who are more susceptible to addiction than members of other gayo community groups. Social media which provides various conveniences and enjoyable effects for students can cause a tendency and dependence in carrying out daily activities. This research aims to analyze the habits of Generation Z students in choosing social media in Takengon City, as well as the media habits of Generation Z students in using social media in Takengon City. This research uses a qualitative descriptive method through a case study approach on six Generation Z students who are highly dependent on social media. Data analysis is carried out by describing or illustrating the data that has been collected as it is without the intention of making generally applicable conclusions. Data collection techniques were carried out through field observation, interviews and documentation which were analyzed descriptively using triangulation techniques. The results of this research show that Generation Z students tend to choose social media platforms that are trendy and popular among teenagers and prefer soft news that is related to their popularity. Generation Z students in Takengon City always provide a special schedule for accessing social media ranging from 3 to 6 hours per day. Generation Z students who actively use social media will be more popular than other students. The presence of social media makes it easier for students to socialize and communicate and build relationships, both from Takengon City and with all students from all universities in Indonesia